The structural integrity of flash-butt welded premium rail steel – Evaluation of strength, microstructure and defects. (September 2021) - Micheletto, Anthony; Cookson, John; Pang, Yong; Chen, Bernard; Mutton, Peter
Experimental testing of flash-butt welded premium rail steel samples was undertaken to quantify the variation in strength through the cross-section of the weld, with results showing a general correlation between the width of the heat-affected-zone and the ultimate tensile strength. Microstructural examination and fractography revealed the presence of defects in some samples. Large defects can be identified by non-destructive testing methods as part of routine structural integrity assessment; however, small defects may escape detection but could propagate under cyclic loading in service leading to catastrophic failures. This work demonstrates the requirement for stringent control of heat input to prevent the development of defects in premium rail steels with high alloying content.